An Investigation into Work-Family Balance and Employee Resilience among Female Bankers: The Mediating role of Organizational Support - Bagire, Vincent; Tauba, Mariam; Kyamulabi , Sarah (SEISENSE Journal of Management, 2023)
Purpose- Work-family balance has increasingly become the epitome of scholarly investigation. This study was motivated to contribute to the growing debate from the Ugandan setting and particularly with a female sample by studying employee resilience. Methods- This study adopted data triangulation conducted among 397 female bankers; where a sample size of 196 was determined. Data was collected using a structured five-point Likert-type scale questionnaire. The instrument was tested for validity using expert opinion and content validity. We also used exploratory factor analysis. For reliability, we used the Cronbach alpha coefficients. The data were collected with the approval and consent of the Research Committee of MUBS, and the supervisors in the banks, and respondents were assured of confidentiality. Findings- Indeed, some organizations have mainstreamed gender into their operations in the footsteps of national gender policy. But work-life balance is beyond gender frameworks. This study found that organizational support has a partial mediation effect between work-family balance and employee resilience. This means that both factors are important in influencing the employee resilience of female workers in the banking sector. Originality-This study is grounded in the practical insights of female bankers in Uganda. While there may be similar studies none has taken a rigorous scholarly approach like this in conceptualization and methodology. This study was original in the context in which it was executed and the methodologies used.   We contend that this study has made a significant contribution to further delineating the life-balance debate for policy, practice, and academic advancements in the African context.